Evaluation of a training programme to foster employability skills in professional training: A case study - Sánchez-Ramírez, José Manuel; Íñigo, Victoria; Marcano, Beatriz; Romero-García, Carmen (Education + Training, 2025)
Purpose: The aim of this work is to evaluate the effectiveness of a training program for developing employability skills including digital competency and soft skills (problem-solving, teamwork, adaptability, leadership, decision making and creativity) in professional-training programs. Design: It presents a case study, where students from a professional training center were evaluated twice, before and after doing the program. The results from both were compared to determine whether there have been improvements. We also analyzed whether there were differences by gender in the pretest and the posttest. Results: We observed that most of the students improved in both digital competency and in soft skills after completing the program. In the case of digital competency, greater improvement was apparent in the areas of collaboration and communication and in digital content creation. Similar results were found for all competencies in the case of soft skills. Originality-value: This learning program had a positive impact on the competency development of professional-training students. Continuous training and advice for teachers and personalized monitoring during the implementation of this program resulted in an improvement being apparent in students’ employability skills.
Keywords: Digital skills; Soft Skills; Vocacional Training; Scopus; JCR